2020
DOI: 10.1371/journal.pone.0229135
|View full text |Cite
|
Sign up to set email alerts
|

Lactate indices as predictors of in-hospital mortality or 90-day survival after admission to an intensive care unit in unselected critically ill patients

Abstract: BackgroundWe performed an exclusive study to investigate the associations between a total of 23 lactate-related indices during the first 24h in an intensive care unit (ICU) and in-hospital mortality. MethodsNine static and 14 dynamic lactate indices, including changes in lactate concentrations (Δ Lac) and slope (linear regression coefficient), were calculated from individual critically ill patient data extracted from the Multiparameter Intelligent Monitoring for Intensive Care (MIMIC) III database. ResultsData… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Lactate clearance has previously been investigated as a potential prognostic marker for sepsis/septic shock 7 , 9 , 15 , 20 . However, increased lactate clearance is not always associated with decreased mortality in sepsis/septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate clearance has previously been investigated as a potential prognostic marker for sepsis/septic shock 7 , 9 , 15 , 20 . However, increased lactate clearance is not always associated with decreased mortality in sepsis/septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…We used logistic regression analysis to test the association between lactate clearance and 28-day mortality in patients with TBIL < 2 mg/dL or ≥ 2 mg/dL. Multivariate analysis was performed to adjust for potential baseline imbalances (age, sex, and Acute Physiology and Chronic Health Evaluation II (APACHE II) score), as reported previously 9 , 20 22 . Creatinine (Cre) level (< and ≥ 2 mg/dL), platelet count (< and ≥ 80 × 10 3 /mm 3 ), and APACHE II score (< and ≥ 35) were also analyzed to evaluate the association between severity and organ dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study of lactate clearance in septic shock patients, strati ed by hepatic dysfunction, increased lactate clearance in the initial 24 hours was signi cantly associated with decreased mortality in patients with TBIL ≥ 2 mg/dL. In contrast, lactate clearance was not associated with altered mortality in patients with TBIL < 2 mg/dL Lactate clearance has been substantially studied as a prognostic marker in sepsis/septic shock [7,9,15,20]. However, increased lactate clearance has not always been observed to be associated with decreased mortality in sepsis/septic shock.…”
Section: Discussionmentioning
confidence: 57%
“…In other unselected cohorts of ICU patients, mortality was higher in patients developing high lactate levels after more than 24 hours following ICU admission or missing lactate clearance in the first 12 hours 3 and lactate at 24 hours after admission to ICU was strongest for prediction of mortality 18 . There are systematic reviews available, that found that across different ICU cohorts lactate clearance was associated with a better outcome 19,20 ; the significance of the course of lactate was thereby independent of the initial value and it was recommended to monitor the lactate level by measurements every 1 to 2 hours 21 .…”
Section: Discussionmentioning
confidence: 83%